Towards the large area HVCMOS demonstrator for ATLAS ITk - Prathapan, Mridula; Weber, Alena (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2019)
High Voltage CMOS (HVCMOS) sensor is a proposed cost effective alternative to the existing hybrid sensors in ATLAS ITk pixel barrel for outer layers. To prove the feasibility of HVCMOS sensors in ATLAS experiment, a large area demonstrator chip is being designed. This work presents the design details of three HVCMOS sensor chips with an overview of the measurement results of ATLASpix1 which is the first large area (1 cm × 2 cm) prototype in 0.18μm process.
Available online 17 November 2018
Gesehen am 09.07.2019